Lightweight Ionic Networks Composed of Li+ or Mg2+ Centres Linked Together by Dicarboxylate Ligands. Issue 8 (5th July 2016) - White, Keith F.; Abrahams, Brendan F.; Hudson, Timothy A.; Robson, Richard
Abstract: The combination of lightweight metal cations with a range of dicarboxylate ligands has led to the generation of ionic network materials that possess channels occupied by solvent molecules. The compounds [Li2 (2, 2‐bpdc)(DMF)2 ] and [Mg(2, 2‐bpdc)(DMF)2 ] (2, 2‐bpdc=2, 2‐dipyridyl‐4, 4‐dicarboxylate) adopt a similar structure in which parallel metal–carboxylate chains are linked to four equivalent chains to generate a 3 D network in which DMF molecules occupy channels. [Li4 (3, 5‐pdc)2 (DMF)]⋅solvate (3, 5‐pdc=3, 5‐pyridine dicarboxylate) adopts a similar structure but the chains are more complex. As with the other structures, coordinated DMF molecules occupy network channels. [Li4 (3, 5‐pdc)2 (DMF)]⋅solvate is able to adsorb carbon dioxide at elevated pressures with the adsorption following a type V isotherm; hysteresis is apparent upon desorption. The final compound, Li[Mg3 OH(2, 2‐bqdc)3 (DMF/H2 O)3 ]⋅solvate (2, 2‐bqdc=2, 2‐biquinoline‐4, 4‐dicarboxylate) has a distinctly different structure in which a trio of magnesium centres bound to a central μ3 ‐hydroxide ion serves as a 6‐connecting, trigonal prismatic node within a 3 D network that has the point symbol, 4 9 6 6 . Solvent‐filled intraframework spaces represent over 50 % of the crystal volume and are occupied by highly disordered solvent and Li + ions. Immersion of Li[Mg3 OH(2, 2‐bqdc)3 (DMF/H2 O)3 ]⋅solvate in a solution of Fe(2, 2‐bipyridine)3 2+ results in the incorporation of the Fe II complex into the large channels of the anionic network. Abstract : Let′s link up : Dicarboxylate ligands have been used to link metal centres such as Li + and Mg 2+ to form 3 D networks (see figure) in which solvent is located in the channels. One of the lithium‐based networks exhibits significant hysteresis in its adsorption of CO2 whilst an anionic magnesium network is able to exchange its Li + countercations for Fe(2, 2‐bipyridine)3 2+ .